Introduction to solid mechanics : an integrated approach - Lubliner, Jacob; Papadopoulos, Panayiotis (Springer, 2016)
This expanded second edition presents in one text the concepts and processes covered in statics and mechanics of materials curricula following a systematic, topically integrated approach. Building on the novel pedagogy of fusing concepts covered in traditional undergraduate courses in rigid-body statics and deformable body mechanics, rather than simply grafting them together, this new edition develops further the authors' very original treatment of solid mechanics with additional figures, an elaboration on selected solved problems, and additional text as well as a new subsection on viscoelasticity in response to students' feedback. Introduction to Solid Mechanics: An Integrated Approach, Second Edition, offers a holistic treatment of the depth and breadth of solid mechanics and the inter-relationships of its underlying concepts. Proceeding from first principles to applications, the book stands as a whole greater than the sum of its parts.- Resumé vydavatel